Comprehensive evaluation of Actinidia arguta fruit based on the nutrition and taste: 67 germplasm native to Northeast China - Mengting Song; Heran Xu; Guang Xin; Changjiang Liu; Xiaorong Sun; Yinhong Zhi; Bin Li; Yixiao Shen (Food Science and Human Wellness)
Actinidia arguta is a berry fruit with high nutritional values. To evaluate the comprehensive quality, the fruit weight, titratable acid (TAC), soluble solids (SSC), vitamin C, mineral elements, and taste value of 67 accessions of A. arguta were measured, and sensory attributes including olfactive intensity, juiciness, sweetness, sourness, and astringency were assessed. Cluster analysis was carried out based on mineral elements, and principal component analysis (PCA) was used for comprehensive score ranking. The result demonstrated that fruit weight ranged from 3.5 g to 24.2 g, SSC ranged from 11.94% to 20.56%, TAC ranged from 0.15% to 1.20%, and vitamin C ranged from 3.51 g/kg to 230.76 g/kg (fresh weight) among the tested samples. There were significant differences in sourness, sweetness, bitterness, and umami among the 67 accessions based on electronic tongue analysis, and this result was rapidly and objectively characterized by the sensory assessment. The dendrogram was obtained and clustered the accessions into two major clusters, and five principal components were extracted by PCA. Overall, the information provided by this study identified the 10 best germplasm resources for fresh-eating and processing fruits. It can provide theoretical reference for nutritional efficacy evaluation and food development of A. arguta.